Sustainability and Competitiveness of Logistics Services Providers in Indonesia - Engkos Achmad Kuncoro; Dony Saputra; Robin Cahyadi; Ridho Bramulya Ikhsan (Bina Nusantara University, 2021)
With the rise of competition and challenges for Logistics Service Providers (LSP) in Indonesia, competitiveness and sustainability are needed. The research explored logistical process and identified factors that built the competitiveness of LSP, such as Third-Party Logistics (3PL) in Indonesia. The research also identified factors and relationships of their competitiveness and sustainability. The research method was explorative with a qualitativeobservation approach. The applied sampling technique was purposive and snowball. The participants were 10 LSP operating in Indonesia: KÃ¼hne + Nagel, FedEx, Damco, DB Schenker, APL Logistics, Panalpina, Agility Logistics, TNT Express, RÃ¶hlig Logistic, and Rhenus Logistic. The data were unstructured interviews with 10 middle managers with the job position of leader and manager. Then, the data were analyzed using NVivo 10 software. The result is the recommendation of the competitiveness model for 3PL that the providers can apply to achieve its sustainability. Moreover, the factors that drive competitiveness of LSP are price, service, people, and network. Meanwhile, innovation and credibility improve competitiveness toward sustainability of 3PL. Based on the findings, it can offer opportunities for further research on the relationship and influence of these variables on other similar companies in other countries.